In Vitro Evaluation of Novel Furo[3,2-c]coumarins as Cholinesterases and Monoamine Oxidases Inhibitors - Mariagrazia Rullo; Alice Benzi; Lara Bianchi; Massimo Maccagno; Guglielmo Marcantoni Taddei; Daniela Valeria Miniero; Giuseppe Felice Mangiatordi; Giovanni Lentini; Leonardo Pisani; Giovanni Petrillo; Cinzia Tavani (Molecules)
Coumarin represents a privileged structural motif that is quite common in nature-derived and synthetic bioactive molecules. Some of us have recently described the straightforward preparation of complex furo[3,2-c]coumarins through a sequential double coupling protocol. Aiming at finding novel chemical probes for the modulation of key anti-Alzheimer’s targets, a small subset of furo[3,2-c]coumarin prototypes and their non-aromatic synthetic precursors were tested in vitro as inhibitors of ChEs (acetyl- and butyrylcholinesterase, AChE and BChE) and MAOs (monoamine oxidases A and B, MAO A and MAO B). All compounds were low-micromolar AChE inhibitors devoid of toxic effects against SH-SY5Y cells. Lineweaver-Burk plots and docking simulations suggested mixed-type kinetics for inhibitor 3d (IC50 = 4.1 μM toward AChE). Its promising inhibitory profile encompasses additional, highly selective, activity against monoamine oxidase B, with a submicromolar IC50 value (561 nM).